Nonmetallic material crystal orientation and residual stress optimization method based on Raman frequency shift

By setting up a polarizer in the Raman spectroscopic measurement system and simplifying the stress field, the measurement error and operation complexity problems in the non-equibiaxial residual stress characterization of polycrystalline alumina micro-region are solved, and high-precision and micron-level stresses are achieved Testing improves testing efficiency and accuracy.

CN119198672APending Publication Date: 2024-12-27XI'AN UNIVERSITY OF ARCHITECTURE AND TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411241355.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-05
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

In the prior art, when determining the crystal orientation of polycrystalline alumina based on Raman spectroscopy, there are problems of large measurement errors, complex operation and low testing efficiency, especially in the characterization of non-isometric biaxial residual stress of micro-region, 95% Al2O3. The low signal-to-noise ratio of Raman spectroscopy and the lack of peak value lead to large stress measurement errors.

Method used

By setting a half-wave plate in the common optical path of incident laser and scattering Raman signals, changing the polarization direction, building a measurement system with 95% Al2O3 crystal orientation, simplifying the stress field, introducing a differential evolution algorithm, and reducing the number of Raman peak frequency shifts. This improves the orientation measurement accuracy and stability of stress solving.

Benefits of technology

Quasi-in-situ stress testing with lossless and micron-level spatial resolution is realized, reducing experimental complexity and data processing difficulty, and improving the accuracy and stability of alumina crystal orientation and residual stress measurement.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119198672A_ABST
    Figure CN119198672A_ABST
Patent Text Reader

Abstract

The invention relates to a Raman frequency shift-based non-metallic material crystal orientation and residual stress optimization method, which comprises the following steps of: building an angular resolution polarization Raman test system of a non-metallic material, adding a polarizer in a laser incident light path and adding a polarization analyzer in a scattering light path by a laser Raman spectrometer, parallel and vertical polarization configuration of a Raman test light path is realized by adjusting polarization directions of incident light and scattered light to be parallel and vertical; distribution functions of polarization Raman signal intensity under different orientation angles under parallel and vertical polarization configuration of a Raman test light path are obtained, and the light intensity is corrected to realize alumina crystal orientation measurement to obtain a polycrystalline alumina Raman spectrum signal-to-noise ratio; optimizing test parameters of the angular resolution polarization Raman test system based on the polycrystalline alumina Raman spectrum signal-to-noise ratio; the calculation precision of alumina residual stress Raman testing is improved through a surface stress field and Raman peak selection, so that residual stress characterization is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of material residual stress and crystal orientation determination, and in particular to a method for optimizing the crystal orientation and residual stress of non-metallic materials based on Raman frequency shift. Background Art

[0002] Non-metallic materials such as glass and ceramics have excellent chemical stability, thermal stability and high-temperature strength, and can work normally in extreme environments under accident conditions. In particular, ceramic-metal brazing seals composed of polycrystalline Al2O3 have become the preferred sealing structure for HTR primary circuit electrical penetrations and are widely used in nuclear power safety equipment. However, when the brazing interface is well bonded, the brazed joint generally fails first on the side of the ceramic close to the weld. Therefore, realizing micro-area stress characterization on the ceramic side and performing stress regulation is a key technology for developing high-strength metal / ceramic brazed joints and ensuring the safe service of nuclear electrical penetrations. At present, there are very few studies on the characterization of micro-area non-equibiaxial residual stress of polycrystalline alumina, which leads to a large number of studies that only qualitatively judge the role of stress regulation methods by joint strength. Accurate characterization of ceramic micro-area stress can provide reliable theoretical guidance for stress regulation methods in brazing process research, which is conducive to the safe service of joints. At present, the methods for characterizing surface residual stress of non-metallic materials are mainly divided into destructive methods (indentation crack method) and non-destructive methods (such as Raman spectroscopy, XRD, and fluorescence spectroscopy). Among them, Raman spectroscopy has good application prospects in the characterization of residual stress in micro-areas of alumina ceramics due to its micron-level resolution and ability to calculate non-equibiaxial residual stress.

[0003] The existing technology still has application problems in determining the crystal orientation of polycrystalline alumina based on Raman spectroscopy and establishing the relationship between stress / strain and Raman frequency shift with clear physical meaning: the model measurement of crystal orientation requires rotating the sample to collect the polarized Raman scattering intensity at different polarization rotation angles, but in order to ensure the reliability of the measurement point results, the measurement point position is required to always coincide with the sample rotation center, which is difficult to operate and has low test efficiency; the theoretical model is a high-order nonlinear equation group, and the complete solution of the crystal strain tensor requires the Raman spectrum to provide at least 6 accurate Raman peak frequency shifts, which is complex to solve and has large error transmission. The Raman spectrum of 95% Al2O3 has low signal-to-noise ratio and peak loss. Direct application of the theoretical model has problems such as difficulty in solving the equation group and large stress measurement errors.

[0004] The above information disclosed in this Background section is only for enhancement of understanding of the background of the invention and therefore it may contain information that does not form the prior art that is already known to a person of ordinary skill in the art. Summary of the invention

[0005] The present invention provides a method for optimizing the crystal orientation and residual stress of non-metallic materials based on Raman frequency shift. By setting a half-wave plate in the common optical path of the incident laser and the scattered Raman signal to change their polarization directions at the same time, a measurement system for 95% Al2O3 crystal orientation is constructed, thereby avoiding the test error and cumbersome operation caused by rotating the sample. According to the optical path configuration, the distribution function of the polarized Raman scattered light intensity with respect to the polarization rotation angle and the crystal orientation angle is re-derived, and the light intensity correction method is improved by comparison to improve the orientation measurement accuracy. By simplifying the stress field, selecting Raman peaks, and introducing a differential evolution algorithm, the number of Raman peak frequency shifts required for solving the equation is reduced to 3, which solves the problem of difficulty in calculating residual stress when the Raman spectrum lacks peaks, and improves the stability and accuracy of stress solution.

[0006] A method for optimizing crystal orientation and residual stress of non-metallic materials based on Raman frequency shift includes:

[0007] S1. Build an angle-resolved polarization Raman test system for non-metallic materials, in which a laser Raman spectrometer adds a polarizer to the laser incident light path and an analyzer to the scattered light path, and realizes the parallel and vertical polarization configuration of the Raman test light path by adjusting the polarization directions of the incident light and the scattered light to be parallel and perpendicular to each other;

[0008] S2. Obtain the distribution function of the polarized Raman signal intensity at different orientation angles under the parallel and vertical polarization configurations of the Raman test light path, and correct the light intensity to achieve the measurement of the orientation of the alumina crystal to obtain the signal-to-noise ratio of the polycrystalline alumina Raman spectrum. During the test process, the Raman spectrum test is performed at intervals of 10° within the range of the polarization rotation angle of 0 to 180°;

[0009] S3, optimizing the test parameters of the angle-resolved polarized Raman test system based on the signal-to-noise ratio of the polycrystalline alumina Raman spectrum;

[0010] S4. Improve the calculation accuracy of Raman testing of aluminum oxide residual stress through surface stress field and Raman peak selection to achieve residual stress characterization.

[0011] In the Raman frequency shift-based non-metallic material crystal orientation and residual stress optimization method, in S2, the calculation expression of the distribution function of the relationship between light intensity and orientation angle under the Raman test light path is:

[0012] (1)

[0013] (2)

[0014] (3)

[0015] (4)

[0016] (5)

[0017] (6)

[0018] In the formula and The vibration mode is α-Al 2 O 3 The corresponding Raman peak position in The vibration modes are divided into and , collected The Raman signal intensity corresponding to the vibration mode is the cumulative intensity of the two. The superscripts ⊥ and ∥ represent the light intensity under parallel polarization and perpendicular polarization configurations, respectively. is the angle between the fast axis of the polarizer and the X direction of the coordinate system. The constants a, b, c and d are the RTEs (Raman tensor elements) determined by the crystal structure of aluminum oxide. , , The coordinate system is converted to the crystallographic coordinate system according to The three Euler angles of the inward rotation rule correspond to its crystallographic orientation.

[0019] In the Raman frequency shift-based non-metallic material crystal orientation and residual stress optimization method, in S2, the intensity-corrected Euclidean norm normalization formula is:

[0020] (7)

[0021] In the formula represents the index of the Raman peak, ; The subscript indicates the index of the polarizer rotation angle, and the total number of rotations is M.

[0022] In the above-mentioned method for optimizing crystal orientation and residual stress of non-metallic materials based on Raman frequency shift, in S2, the calculation formula for the total residual between the measured distribution value corrected by Raman light intensity and the theoretical distribution value is:

[0023] R e s = ∑ J ∑ i M oh J 2 [ I J f i t t e d ( ψ i ) − I J d a t a ( ψ i ) ] 2 (8)

[0024] In the formula represents the index of the Raman peak, ; Subscript Indicates the rotation angle of the polarizer The index of , the total number of rotations is M; is calculated by fitting at the rotation angle Raman Peak The relative strength of is obtained by testing the rotation angle Raman Peak The relative strength of is the weight factor introduced when calculating the residual corresponding to the Raman peak, The purpose of introducing the weight factor is to standardize the residual using the intensity of the Raman peak so that the crystal orientation calculation process , , and The residuals have the same weight.

[0025] In the method for optimizing the crystal orientation and residual stress of non-metallic materials based on Raman frequency shift, in S4, the Raman frequency shift With α-Al 2 O 3 Strain tensor in crystallographic coordinate system The functional relationship between them is

[0026] { D w A = w A − w 0 , A = 1 2 w 0 , A ( K 1 A ϵ 1 1 + K 2 A ϵ 2 2 + K 3 A ϵ 3 3 ) D w E = w E − w 0 , E = 1 2 w 0 , E [ K 1 E ( ϵ 1 1 + ϵ 2 2 ) + K 2 E ϵ 3 3 ± [ K 3 E ( ϵ 1 1 − ϵ 2 2 ) + K 4 E ϵ 1 3 ] 2 + ( K 3 E ϵ 1 2 + K 4 E ϵ 2 3 ) 2  ] (9)

[0027] In the formula and express Raman peak positions of vibration modes under stress and stress-free conditions; and In Raman spectroscopy Raman peak positions of vibration modes under stress and stress-free conditions; and Corresponding to α-Al 2 O 3 middle and PDP constant of the vibration mode; is the strain tensor in the crystallographic coordinate system, subscript and Corresponding to α-Al 2 O 3 The direction of the main axis of the crystal.

[0028] In the Raman frequency shift-based non-metallic material crystal orientation and residual stress optimization method, α-Al 2 O 3 It is a trigonal crystal structure, and its stress tensor and strain tensor in the crystallographic reference system follow the equation

[0029] (10)

[0030] In the formula are elastic stiffness constants, respectively , , , , and , the unit is 10 12 dyn / cm 2 , that is 10 11 Pa,

[0031] When the crystal orientation ( ) is known, the crystallographic stress tensor can be obtained by Euler transformation Conversion to laboratory stress tensor ,

[0032] (11).

[0033] In the Raman frequency shift-based non-metallic material crystal orientation and residual stress optimization method, a set of optimal orientation angles ( ), so that the total residual between the measured distribution and the theoretical distribution of Raman intensity under this orientation is minimized.

[0034] In the Raman frequency shift-based non-metallic material crystal orientation and residual stress optimization method, the test parameters are optimized by the signal-to-noise ratio (SNR) of the Raman spectrum and the test efficiency. The calculation of SNR is shown in the formula

[0035] ,

[0036] The unit of signal-to-noise ratio SNR is dB; (signal) and (noise) respectively represent the variance of the signal segment after baseline subtraction of the original spectrum, i.e., the area covered by the Raman peak, and the noise segment, i.e., the area not covered by the Raman peak.

[0037] In the Raman frequency shift-based non-metallic material crystal orientation and residual stress optimization method, the test parameters include relative laser power and exposure time, a 2-factor 3-level experiment was carried out, and a single-factor experiment with 1, 2 and 4 repeated acquisition times was performed to determine the experimental parameters corresponding to the spectrum obtained when the Raman method is used to measure residual stress, namely, a relative laser power of 100%, an exposure time of 6 s, and a repeated acquisition number of 2 times.

[0038] In the non-metallic material crystal orientation and residual stress optimization method based on Raman frequency shift, the polarizer is a half-wave plate and the analyzer is a quarter-wave plate.

[0039] Compared with the prior art, the present invention has the following advantages: the present invention sets a polarizer in the common optical path of the incident laser and the scattered Raman signal, thereby building a measurement system for the 95% Al2O3 crystal orientation, avoiding the orientation test error and cumbersome operation caused by the rotating sample; and re-derives the distribution function of the polarized Raman scattered light intensity with respect to the polarization rotation angle and the crystal orientation angle according to the optical path configuration, and improves the light intensity correction method by comparison to improve the orientation measurement accuracy. In addition, the method reduces the number of Raman peak frequency shifts required for equation solution to 3 by simplifying the stress field, selecting Raman peaks, and introducing differential evolution algorithms, which solves the problem that it is difficult to calculate residual stress when the Raman spectrum lacks peaks, improves the stability and accuracy of stress solution, and provides practical application guidance for measuring 95% Al2O3 residual stress based on Raman frequency shift. Non-destructive, micron-level spatial resolution and quasi-in-situ stress testing are achieved. The method optimizes the calculation method without reducing the test accuracy, thereby reducing the complexity of the experiment and data processing process. The use of Raman spectroscopy can more conveniently and accurately characterize the crystal orientation and residual stress of 95% aluminum oxide. This method has broad application prospects and application guidance in the fields of non-metallic materials, structural analysis and failure analysis. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] By reading the detailed description of the preferred specific embodiments below, various other advantages and benefits of the present invention will become clear to those of ordinary skill in the art. The drawings in the specification are only for the purpose of illustrating the preferred embodiments and are not considered to be limitations of the present invention. Obviously, the drawings described below are only some embodiments of the present invention. For those of ordinary skill in the art, other drawings can also be obtained based on these drawings without creative work. Moreover, the same reference numerals are used to represent the same components throughout the drawings.

[0041] In the attached picture:

[0042] Figure 1 This is a schematic diagram of pre-stressing a stressed sample to be tested according to the present invention;

[0043] Figure 2 This is a schematic diagram of the configuration of the polarized Raman optical path of the present invention;

[0044] Figures 3(a) to 3(c) are schematic diagrams showing the effects of Raman test parameters on the signal-to-noise ratio of Raman spectra. Figure 3(a) shows the effect of relative laser power on the signal-to-noise ratio of Raman spectra, Figure 3(b) shows the effect of exposure time on the signal-to-noise ratio of Raman spectra, and Figure 3(c) shows the effect of exposure time on the signal-to-noise ratio of Raman spectra.

[0045] Figure 4 Schematic diagram of the Euler rotation process for transforming the experimental coordinate system into the crystallographic coordinate system (ZX'Z'' internal rotation);

[0046] Figures 5(a) to 5(b) are the intensity fitting and crystal orientation calculation results (sapphire C plane) under the Euclidean norm normalization method. Figure 5(a) is the intensity fitting result, and Figure 5(b) is the orientation calculation result.

[0047] Figure 6 This is the stress solution flow chart;

[0048] Figure 7 (a) to Figure 7 (b) are the Raman test positions and surface morphologies of the non-equibiaxial and uniaxial residual stresses of polycrystalline alumina. Figure 7 (a) is the Raman spectrum field of view test position, and Figure 7 (b) is the optical microscope field of view test position.

[0049] The present invention is further explained below in conjunction with the accompanying drawings and embodiments. DETAILED DESCRIPTION

[0050] The specific embodiments of the present invention will be described in more detail below with reference to the accompanying drawings. Although the specific embodiments of the present invention are shown in the accompanying drawings, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided in order to enable a more thorough understanding of the present invention and to fully convey the scope of the present invention to those skilled in the art.

[0051] It should be noted that certain words are used in the specification and claims to refer to specific components. Those skilled in the art should understand that technicians may use different nouns to refer to the same component. This specification and claims do not use the difference in nouns as a way to distinguish components, but use the difference in the functions of the components as the criterion for distinction. As mentioned throughout the specification and claims, "including" or "comprising" is an open term, so it should be interpreted as "including but not limited to". The subsequent description of the specification is a preferred embodiment of the present invention, but the description is based on the general principles of the specification and is not intended to limit the scope of the present invention. The scope of protection of the present invention shall be determined by the attached claims.

[0052] To facilitate understanding of the embodiments of the present invention, further explanation will be given below by taking specific embodiments as examples in conjunction with the accompanying drawings, and each of the accompanying drawings does not constitute a limitation on the embodiments of the present invention.

[0053] like Figure 1 As shown in FIG7( b ), the method for optimizing the crystal orientation and residual stress of non-metallic materials based on Raman frequency shift includes the following steps:

[0054] S1. Build an angle-resolved polarization Raman test system for non-metallic materials, in which a laser Raman spectrometer adds a polarizer to the laser incident light path and an analyzer to the scattered light path, and realizes the parallel and vertical polarization configuration of the Raman test light path by adjusting the polarization directions of the incident light and the scattered light to be parallel and perpendicular to each other;

[0055] S2. Obtain the distribution function of the polarized Raman signal intensity at different orientation angles under the parallel and vertical polarization configurations of the Raman test light path, and correct the light intensity to achieve the measurement of the orientation of the aluminum oxide crystal to obtain the signal-to-noise ratio of the Raman spectrum of polycrystalline aluminum oxide. During the test process, the Raman spectrum test is performed at intervals of 10° within the range of the polarization rotation angle of 0 to 180°;

[0056] S3, optimizing the test parameters of the angle-resolved polarized Raman test system based on the signal-to-noise ratio of the polycrystalline alumina Raman spectrum;

[0057] S4. Improve the calculation accuracy of Raman testing of aluminum oxide residual stress through surface stress field and Raman peak selection to achieve residual stress characterization.

[0058] In a preferred embodiment of the method for optimizing the crystal orientation and residual stress of non-metallic materials based on Raman frequency shift, in S2, the calculation expression of the distribution function of the relationship between the light intensity and the orientation angle under the Raman test light path is:

[0059] (1)

[0060] (2)

[0061] (3)

[0062] (4)

[0063] (5)

[0064] (6)

[0065] In the formula and The vibration mode is α-Al 2 O 3 The corresponding Raman peak position in The vibration modes are divided into and , collected The Raman signal intensity corresponding to the vibration mode is the cumulative intensity of the two. The superscripts ⊥ and ∥ represent the light intensity under parallel polarization and perpendicular polarization configurations, respectively. is the angle between the fast axis of the polarizer and the X direction of the coordinate system. The constants a, b, c and d are the RTEs (Raman tensor elements) determined by the crystal structure of aluminum oxide. , , The coordinate system is converted to the crystallographic coordinate system according to The three Euler angles of the inward rotation rule correspond to its crystallographic orientation.

[0066] In a preferred embodiment of the method for optimizing the crystal orientation and residual stress of non-metallic materials based on Raman frequency shift, in S2, the normalized formula of the Euclidean norm of light intensity correction is:

[0067] (7)

[0068] In the formula represents the index of the Raman peak, ; The subscript indicates the index of the polarizer rotation angle, and the total number of rotations is M.

[0069] In a preferred embodiment of the method for optimizing the crystal orientation and residual stress of non-metallic materials based on Raman frequency shift, in S2, the calculation formula for the total residual between the measured distribution value corrected by Raman light intensity and the theoretical distribution value is:

[0070] R e s = ∑ J ∑ i M oh J 2 [ I J f i t t e d ( ψ i ) − I J d a t a ( ψ i ) ] 2 (8)

[0071] In the formula represents the index of the Raman peak, ; Subscript Indicates the rotation angle of the polarizer The index of , the total number of rotations is M; is calculated by fitting at the rotation angle Raman Peak The relative strength of is obtained by testing the rotation angle Raman Peak The relative strength of is the weight factor introduced when calculating the residual corresponding to the Raman peak, The purpose of introducing the weight factor is to standardize the residual using the intensity of the Raman peak so that the crystal orientation calculation process , , and The residuals have the same weight.

[0072] In a preferred embodiment of the method for optimizing the crystal orientation and residual stress of non-metallic materials based on Raman frequency shift, in S4, the Raman frequency shift With α-Al 2 O 3 Strain tensor in crystallographic coordinate system The functional relationship between them is

[0073] { D w A = w A − w 0 , A = 1 2 w 0 , A ( K 1 A ϵ 1 1 + K 2 A ϵ 2 2 + K 3 A ϵ 3 3 ) D w E = w E − w 0 , E = 1 2 w 0 , E [ K 1 E ( ϵ 1 1 + ϵ 2 2 ) + K 2 E ϵ 3 3 ± [ K 3 E ( ϵ 1 1 − ϵ 2 2 ) + K 4 E ϵ 1 3 ] 2 + ( K 3 E ϵ 1 2 + K 4 E ϵ 2 3 ) 2  ] (9)

[0074] In the formula and express Raman peak positions of vibration modes under stress and stress-free conditions; and In Raman spectroscopy Raman peak positions of vibration modes under stress and stress-free conditions; and Corresponding to α-Al 2 O 3 middle and PDP constant of the vibration mode; is the strain tensor in the crystallographic coordinate system, subscript and Corresponding to α-Al 2 O 3 The direction of the main axis of the crystal.

[0075] In a preferred embodiment of the Raman frequency shift-based non-metallic material crystal orientation and residual stress optimization method, α-Al 2 O 3 It is a trigonal crystal structure, and its stress tensor and strain tensor in the crystallographic reference system follow the equation

[0076] (10)

[0077] In the formula are the elastic stiffness constants, respectively , , , , and , the unit is 10 12 dyn / cm 2 , that is 10 11 Pa,

[0078] When the crystal orientation ( ) is known, the crystallographic stress tensor can be obtained by Euler transformation Conversion to laboratory stress tensor ,

[0079] (11).

[0080] In a preferred embodiment of the Raman frequency shift-based non-metallic material crystal orientation and residual stress optimization method, a set of optimal orientation angles ( ), so that the total residual between the measured distribution and the theoretical distribution of Raman intensity under this orientation is minimized.

[0081] In a preferred embodiment of the method for optimizing crystal orientation and residual stress of non-metallic materials based on Raman frequency shift, the test parameters are optimized by the signal-to-noise ratio (SNR) of Raman spectroscopy and the test efficiency. The calculation of SNR is shown in the formula

[0082] ,

[0083] The unit of signal-to-noise ratio SNR is dB; (signal) and (noise) respectively represent the variance of the signal segment after baseline subtraction of the original spectrum, i.e., the area covered by the Raman peak, and the noise segment, i.e., the area not covered by the Raman peak.

[0084] In the preferred embodiment of the method for optimizing the crystal orientation and residual stress of non-metallic materials based on Raman frequency shift, the test parameters include relative laser power and exposure time, a 2-factor 3-level experiment was carried out, and a single-factor experiment with 1, 2 and 4 repeated acquisition times was performed to determine the experimental parameters corresponding to the spectrum obtained when the Raman method is used to measure residual stress, namely, a relative laser power of 100%, an exposure time of 6 s, and a repeated acquisition number of 2 times.

[0085] In a preferred implementation of the method for optimizing the crystal orientation and residual stress of non-metallic materials based on Raman frequency shift, the polarizer is a half-wave plate and the analyzer is a quarter-wave plate.

[0086] In one embodiment, facing the phenomenon that 95% of the aluminum oxide Raman peaks are missing and stress solution is difficult, the solution process is simplified. Considering that the characterization depth of laser confocal Raman spectroscopy is only a few microns deep on the aluminum oxide surface, it can be considered that Raman spectroscopy only measures the surface residual stress of aluminum oxide, and the stress component related to the detection depth direction is , and When all are 0, there are only three stress components to be solved, and we only need to select the frequency shifts of any three Raman peaks to construct the stress calculation equation group.

[0087] (13)

[0088] The Euclidean norm normalization method is used to correct the measured Raman light intensity distribution data, effectively reducing the crystal orientation calculation error caused by test abnormal values. A set of optimal orientation angles ( ), so that the total residual between the measured distribution and the theoretical distribution of Raman light intensity under this orientation is minimized. According to the different changing trends of the peak positions in the measured Raman spectra under different polarization rotation angles, two sets of peak selection schemes with easy calibration of peak positions are given, Scheme A (378 cm-1, 417 cm-1 and 750 cm-1) and Scheme B (417 cm-1, 576 cm-1 and 750 cm-1). The two schemes are used for residual stress calculation respectively, and it is found that Scheme B has significantly higher test accuracy.

[0089] In one embodiment, a specific case is taken as an example: taking the characterization of uniaxial and non-equibiaxial residual stress of 95% Al2O3 as an example, a Raman experiment is performed on a 95% Al2O3 sample with a known pre-stress through a tooling, and the experimental parameters are set to 100% relative laser power, 6s exposure time, and 2 repeated acquisition times. Figures 7 (a) to 7 (b) show the distribution of surface measurement points in the field of view of the Raman spectrometer under pre-applied uniaxial (-118 MPa / 0MPa) and non-equibiaxial (-118 MPa / -62MPa) residual stresses, and the measurement point step size is 5 μm. Figure 7 (b) shows the measurement point A under the field of view of an optical microscope. 1 ~A 13 The ceramic surface morphology near the column, the test position is in a dot matrix form with a total of 39 test points.

[0090] Table 1 shows the average residual stress measurement values ​​of each column of measurement points for pre-applied non-equibiaxial (-118 MPa / -62MPa). Among the thirteen columns of results, only eight columns in the table have measured stress values, and the rest of the measurement results are almost 0. This is related to the porous structure of polycrystalline alumina. Holes may appear below the measurement position, causing stress singularity. However, through the existing measurement values, it can be found that after the increase in the number of measurement points, the stress measurement values ​​of each measurement point in polycrystalline alumina are less dispersed than the equibiaxial stress measurement values, and the relative error is smaller. The calculated mean value of residual stress at 8 columns of measurement points and They are -108.75MPa and -66.9 MPa respectively, with relative errors of -7.8% and -15.1% respectively.

[0091] Table 2 shows the average residual stress measurement values ​​of each column of measuring points for pre-applied uniaxial (-118 MPa / 0 MPa). The effective value of the measuring point in the stress test result is similar to that of the above non-equibiaxial. Due to the sufficient range and number of measuring points, the stress test value of each measuring point has a low dispersion and a small relative error. The calculated mean residual stress of the 8 columns of measuring points and They are -124.93MPa and -3.24MPa respectively, with a relative error of -5.89%. It can be found that in the calculation of residual stress, the present invention simplifies the stress solution process through the optimization algorithm, but the residual stress calculation accuracy still maintains high precision and high stability, and the calculation is more efficient.

[0092] Table 1 Residual stress measurement results of polycrystalline alumina under non-equibiaxial (-118 MPa / -62 MPa) loading

[0093]

[0094] Table 2 Residual stress measurement results of polycrystalline alumina under uniaxial (-118 MPa / 0 MPa) loading

[0095]

[0096] Although the embodiments of the present invention are described above in conjunction with the accompanying drawings, the present invention is not limited to the above specific embodiments and application fields, and the above specific embodiments are only illustrative and instructive, rather than restrictive. A person of ordinary skill in the art can also make many forms under the guidance of this specification and without departing from the scope of protection of the claims of the present invention, all of which belong to the protection of the present invention.

Claims

1. A method for optimizing crystal orientation and residual stress of non-metallic materials based on Raman frequency shift, characterized in that: The steps include: S1. Build an angle-resolved polarization Raman test system for non-metallic materials, in which a laser Raman spectrometer adds a polarizer to the laser incident light path and an analyzer to the scattered light path, and realizes the parallel and vertical polarization configuration of the Raman test light path by adjusting the polarization directions of the incident light and the scattered light to be parallel and perpendicular to each other; S2. Obtain the distribution function of the polarized Raman signal intensity at different orientation angles under the parallel and vertical polarization configurations of the Raman test light path, and correct the light intensity to achieve the measurement of the orientation of the alumina crystal to obtain the signal-to-noise ratio of the polycrystalline alumina Raman spectrum. During the test process, the Raman spectrum test is performed at intervals of 10° within the range of the polarization rotation angle of 0 to 180°; S3, optimizing the test parameters of the angle-resolved polarized Raman test system based on the signal-to-noise ratio of the polycrystalline alumina Raman spectrum; S4. Improve the calculation accuracy of Raman testing of aluminum oxide residual stress through surface stress field and Raman peak selection to achieve residual stress characterization.

2. The method for optimizing crystal orientation and residual stress of non-metallic materials based on Raman frequency shift according to claim 1, characterized in that: Preferably, in S2, the calculation expression of the distribution function of the relationship between light intensity and orientation angle under the Raman test light path is: (1) (2) (3) (4) (5) (6) In the formula and The vibration mode is the corresponding Raman peak position in α-Al2O3. The vibration modes are divided into and , collected The Raman signal intensity corresponding to the vibration mode is the cumulative intensity of the two. The superscripts ⊥ and ∥ represent the light intensity under parallel polarization and perpendicular polarization configurations, respectively. is the angle between the fast axis of the polarizer and the X direction of the coordinate system. The constants a, b, c and d are the RTEs determined by the crystal structure of aluminum oxide. , , The coordinate system is converted to the crystallographic coordinate system according to The three Euler angles of the inward rotation rule correspond to its crystallographic orientation.

3. The method for optimizing crystal orientation and residual stress of non-metallic materials based on Raman frequency shift according to claim 1, characterized in that: In S2, the Euclidean norm normalization formula for light intensity correction is: (7) In the formula represents the index of the Raman peak, ; The subscript indicates the index of the polarizer rotation angle, and the total number of rotations is M.

4. The method for optimizing crystal orientation and residual stress of non-metallic materials based on Raman frequency shift according to claim 3, characterized in that: In S2, the calculation formula for the total residual between the measured distribution value and the theoretical distribution value after Raman intensity correction is: (8) In the formula represents the index of the Raman peak, ; Subscript Indicates the rotation angle of the polarizer The index of , the total number of rotations is M; is calculated by fitting at the rotation angle Raman Peak The relative strength of is obtained by testing the rotation angle Raman Peak The relative strength of is the weight factor introduced when calculating the residual corresponding to the Raman peak, The purpose of introducing the weight factor is to standardize the residual using the intensity of the Raman peak so that the crystal orientation calculation process , , and The residuals have the same weight.

5. The method for optimizing crystal orientation and residual stress of non-metallic materials based on Raman frequency shift according to claim 1, characterized in that: In S4, the Raman frequency shift The strain tensor in the α-Al2O3 crystallographic coordinate system The functional relationship between them is (9) In the formula and express Raman peak positions of vibration modes under stress and stress-free conditions; and In Raman spectroscopy Raman peak positions of vibration modes under stress and stress-free conditions; and Corresponding to α-Al2O3 and PDP constant of the vibration mode; is the strain tensor in the crystallographic coordinate system, subscript and They correspond to the main axis directions of α-Al2O3 crystal respectively.

6. The method for optimizing crystal orientation and residual stress of non-metallic materials based on Raman frequency shift according to claim 5, characterized in that: α-Al2O3 has a trigonal crystal structure, and its stress tensor and strain tensor in the crystallographic reference system follow the equation (10) In the formula are elastic stiffness constants, respectively , , , , and , the unit is 10 12 dyn / cm 2 , that is 10 11 Pa, When the crystal orientation ( ) is known, the crystallographic stress tensor can be obtained by Euler transformation Conversion to laboratory stress tensor , (11)。 7. The method for optimizing crystal orientation and residual stress of non-metallic materials based on Raman frequency shift according to claim 1, characterized in that: By iterative calculation, a set of optimal orientation angles ( ), so that the total residual between the measured distribution and the theoretical distribution of Raman intensity under this orientation is minimized.

8. The method for optimizing crystal orientation and residual stress of non-metallic materials based on Raman frequency shift according to claim 1, characterized in that: The test parameters are optimized by the signal-to-noise ratio (SNR) of the Raman spectrum and the test efficiency. The calculation of SNR is shown in the formula , The unit of signal-to-noise ratio SNR is dB; (signal) and (noise) respectively represent the variance of the signal segment after baseline subtraction of the original spectrum, i.e., the area covered by the Raman peak, and the noise segment, i.e., the area not covered by the Raman peak.

9. The method for optimizing crystal orientation and residual stress of non-metallic materials based on Raman frequency shift according to claim 1, characterized in that: The test parameters included relative laser power and exposure time. A two-factor three-level experiment was carried out, and a single-factor experiment with 1, 2 and 4 repeated acquisitions was performed to determine the experimental parameters corresponding to the spectrum obtained when the Raman method was used to measure residual stress, namely, relative laser power of 100%, exposure time of 6 s, and repeated acquisition times of 2.

10. The method for optimizing crystal orientation and residual stress of non-metallic materials based on Raman frequency shift according to claim 1, characterized in that: The polarizer is a half-wave plate and the analyzer is a quarter-wave plate.